Integrating Sharia Principles into Portfolio Optimization: Empirical Evidence from the Indonesian Islamic Capital Market - Sisca Debyola Widuhung; Zul Karnen; Yatimin Yatimin (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to analyze the influence of Sharia values in the portfolio optimization process and evaluate their specific contribution to risk and return within the Indonesian Sharia capital market.Methodology: This research used a quantitative approach with a descriptive-associative design. Analyze secondary data (stock prices and financial statements) from companies in the Jakarta Islamic Index (JII) for the 2018–2024 period. The analysis combined the Markowitz portfolio optimization method with multiple linear regression to test the impact of Sharia compliance on performance.Findings: Integrating Sharia values enhances portfolio efficiency, evidenced by higher Sharpe ratios and lower risk levels (11.80% vs 13.50% in traditional models). Furthermore, the regression analysis showed that the Sharia compliance score has a positive and significant impact on portfolio returns, with a coefficient of 0.031 and a p-value of 0.011.Conclusion: Applying Sharia values to portfolio optimization is an adaptive and strategic approach that makes portfolios not only ethical but also financially competitive. The study concludes that Sharia principles serve as a tool for risk mitigation and enhance long-term investment sustainability.